2022
DOI: 10.1182/blood.2021013411
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccination and ITP in patients with de novo or preexisting ITP

Abstract: Cases of de novo immune thrombocytopenia (ITP) - including a fatality - following SARS-CoV-2 vaccination in previously healthy recipients led to studying its impact in pre-existing ITP. In this study, four data sources were analyzed: the Vaccine Adverse Events Reporting System (VAERS) for cases of de novo ITP; a ten-center retrospective study of adults with pre-existing ITP receiving SARS-CoV-2 vaccination; and surveys distributed by the Platelet Disorder Support Association (PDSA, United States) and the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 24 publications
5
94
0
1
Order By: Relevance
“… 4 A subset of 13 patients in this cohort were included in a multicenter retrospective observational study evaluating platelet trends following Covid‐19 immunization among those with a history of ITP. 5 Here, we corroborate findings that approximately half had a drop in platelet count following vaccination, but that intervention was required in a minority of cases. Further, with additional follow‐up data, our study demonstrates that adverse events were rare and platelet decreases were mostly transient.…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“… 4 A subset of 13 patients in this cohort were included in a multicenter retrospective observational study evaluating platelet trends following Covid‐19 immunization among those with a history of ITP. 5 Here, we corroborate findings that approximately half had a drop in platelet count following vaccination, but that intervention was required in a minority of cases. Further, with additional follow‐up data, our study demonstrates that adverse events were rare and platelet decreases were mostly transient.…”
Section: Figuresupporting
confidence: 86%
“…One subject was described in a previously published case report. 4 We also contributed data from this subject and 12 others to a multicenter retrospective observational study 5 ; outcomes in these subjects are described in additional detail and with further follow‐up data here.…”
Section: Figurementioning
confidence: 99%
“…Unlike adenoviral vector vaccines (AstraZeneca/VaxZevria and Janssen/COVID-19), no serious complication of vaccine-induced thrombosis/thrombocytopenia (VIIT) was reported in mRNA vaccines [48]. On the other hand, cases of immune thrombocytopenia appearing in the first 2 weeks after vaccination (usually the first dose) have been reported: 17 cases in the United States in the period January-February 2021 in which 20 million people were vaccinated [49]. Thrombocytopenia immune is also reported for other vaccinations, for example 1:40,000 children vaccinated for measles-rubella-mumps, but the rarity of the recorded events does not allow the distinction between the event induced by vaccination (causal relationship) and event coinciding with vaccination (random relationship), as immune thrombocytopenia occurs in the pediatric or adult population even beyond any temporal correlation with vaccinations.…”
Section: Rare Adverse Eventsmentioning
confidence: 99%
“…Autoimmune responses following other vaccines, including those against Measles, Mumps and Rubella (MMR), Influenza, Polio, and Human Papillomavirus have been previously reported, and molecular mimicry has been implicated as a mechanism of undesired immune responses. Interestingly, the recent COVID-19 vaccination follow-up study of the patients with pre-existing ITP showed higher exacerbation risk in those post-splenectomy and those with more refractory disease [8] . Previous studies reported that resistance to IVIG treatment was more frequent when ITP was caused by anti-GPIb/IX compared to anti-GPIIb-IIIa [9] [10] .…”
mentioning
confidence: 99%
“…In addition, our previous study using mouse models demonstrated that platelet hepatic sequestration and TPO upregulation occurs when platelets are acutely depleted by high-dose anti-GPIbα [5] . Higher exacerbation risk of thrombocytopenia in patients with prior splenectomy [8] may indicate hepatic platelet clearance mediated by anti-GPIbα. Further investigation is warranted to determine the mechanism by which the administration of mRNA vaccine and the expression of spike proteins not only trigger T cell responses against spike proteins but also potentiate the production of anti-GPIbα antibodies.…”
mentioning
confidence: 99%